(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The stucco decoration has received special and continuous care in the architecture of the Arab-Islamic arts, until it reached a great deal of perfection and diversity of the efforts made, and decoration in general is a science of the arts. Islam played its role in the development of art and presented it with a new look that harmonized with the concepts of the new life, knowing that we cannot ignore the previous Sasanian and Byzantine influences of Islamic art that formed an important support in several stages and places. The study here aimed at knowing the techniques of ancient stucco decoration and revealing the developments introduced to the stucco decoration through knowledge of its beginnings, stages of development and places where it was placed in order to reach the goal, from the era of the Holy Prophet through the Umayyad era, which witnessed an evolution in the clear stucco decoration in its buildings and thus the era has come to an end. Austerity in the Arab-Islamic decoration. And the Abbasid era, which witnessed a great development in stucco decoration, and its methods were defined and varied. Then the Fatimid, Ayyubid and Mamluk periods, through Morocco and Andalusia. This overview of some Islamic buildings in different eras enabled us to identify the methods of stucco decoration, which varied between engraving, molding, pressing, glazing and fresco. The research came to confirm that the stucco decoration has formed throughout the ages, one of the episodes of the evolution of the Arab-Islamic decoration.